Redesigning HR Business Processes with Camunda BPMN and Chatbot Integration - Chaerulisma, Hanuga Fathur; Setiani, Novi (Jurnal Sains, Nalar, dan Aplikasi Teknologi Informasi, 2025)
Human Resource Management (HRM) processes such as attendance tracking, bonus management, and employee onboarding are often inefficient due to manual methods that are time-consuming, error-prone, and lack standardisation. This study addresses these issues by implementing the Camunda BPMN Engine and a Telegram-based chatbot, guided by the Agile Business Process and Practice Alignment Methodology (BPPAM). The BPMN engine automates workflows, while the chatbot simplifies interaction, enhancing response time and data accuracy. Significant improvements were observed after implementation. The number of user tasks was reduced. For instance, attendance went from 6 to 0 steps (100% reduction), and onboarding went from 14 to 1 steps (92.86% reduction). Processing times improved as well: attendance dropped from 3–5 minutes to under 2 minutes (60% faster), and bonus approval dropped from over 7 days to less than 1 day (85% reduction). Feedback from employees and HR staff highlighted increased satisfaction due to the system’s speed, ease of use, and standardized workflows. The results demonstrate that integrating BPMN automation with chatbot technology can enhance HR operations by increasing efficiency, accuracy, and user experience. The approach offers a scalable solution aligned with modern organizational needs.